Pengaruh Penerapan Model Problem Based Learning Berbantu Canva Terhadap Hasil Belajar Subtema Kekayaan Sumber Energi Di Indonesia - Auditya, Cory Aulia; Windiyani, Tustiyana; Zen M. F., Dendy Saeful (Jurnal PGSD, 2025)
The Effect of Canva-Assisted Problem Based Learning Model on Learning Outcomes of Energy Source Wealth in Indonesia. Thesis of the Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, 2022. The study is a quasi experimental research that aims to determine the effectiveness of the Canva-assisted Problem Based Learning (PBL) model in improving student learning outcomes on the sub-theme of energy resource wealth in Indonesia. The research was conducted at Margajaya 2 Elementary School, Bogor City, involving Class IV B and IV C during the even semester, starting from June. The N-Gain calculation of the PBL model reached a score of 75, which falls into the hight criteria, with 100% completeness of student learning outcomes. In contrast, the N-Gain value of the conventional learning model was only 41, categorized as low, with a completeness percentage of merely 33%. The results of hypothesis testing indicate that H0 is rejected and Ha is accepted because the value of tcount (8.3993) is higher than ttable (2.004879). Based on these findings, it can be concluded that the Canva-assisted Problem Based Learning model has a significant and positive influence on student learning outcomes. Therefore, this model is considered very effective for learning the sub-theme of energy resource wealth in Indonesia.